Triethanolamine impregnation/steam synergistic softening of teakwood to improve bending properties and its mechanism. Issue 2 (4th March 2023) - Yao, Linghua; Sun, Delin; Wang, Zhangheng; Yu, Minggong
ABSTRACT: Solid wood bending component has good mechanical properties and unique artistic characteristics. To investigate bending properties of solid wood and its mechanism, this paper has conducted the studies of softening and bending teakwood which is chosen as raw material, vacuum impregnation was carried out with environmentally friendly triethanolamine (TEA), sodium chloride (NaCl) and sodium dodecyl benzene sulfonate (SDBS) as compound softening solution, and the wood was softened with superheated steam as the medium. The results show that the infiltration of softening solution can increase the content of O and N elements in the wood and form C-NH2 and C–N bonds with C element. When the concentration of softening solution is 15%(m/m), the wood presents the best bending property, and the bending coefficient can reach 1/9.24, which is 20.48% higher than that of the untreated wood, and the qualification rate of bending components is increased to 85%. After drying and shaping, compression strength parallel to grain and bending strength increased by 22.91% and 20.82%, as well the indentation modulus and hardness of the cell wall increased by 16.70% and 21.45%, respectively. Meanwhile, the wet swelling rate and chord length change rate decreased by 51.39% and 3.37%.